Potensi dan Kelayakan Ekonomi Budidaya Kacang Tanah Pada Sawah Tadah Hujan Di Desa Raddae Kabupaten Wajo - Syamsuri Syamsuri; Hasria Alang (AGRIMOR, 2022)
Peanut cultivation by the people of Raddae Village is carried out after the rice harvest, which is the end of the rainy season. This is done in order to maximize the use of rice fields during the rainy season, before the dry season which is also a period of famine. People in the area practice peanut cultivation, but do not know whether the business is profitable or not. People cultivate peanuts to maximize rice fields when the rainy season arrives. The purpose of the research was to analyze economic potential and business feasibility in Raddae Village, Wajo regency. The sampling technique was carried out by simple random sampling so that 15 samples were obtained. The Economic potential analysis is carried out using the income formula, namely TR-TC, while the business feasibility analysis is calculated using the R/C ratio, BEP, PP, and ROI. The results showed that peanut cultivation in this location has economic potential because it can meet all needs during the farming process, while the results of the feasibility analysis also show that the cultivation is feasible or continued.